Text and context a textual analysis of cohesive devices used in the column court of last retort - Mallari, Rhona Diana B.; Ventura, Eloisa P., adviser (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2002)
This study focuses on the column "Court of Last Retort". The research examines how cohesive devices as well as contexts give coherence to texts. The cohesive devices as discussed by Halliday and Hasan and the Gricean maxims were used to analyze the articles. In this study, it is illustrated that coherence goes beyond what the cohesive devices show. Therefore, coherence is a product of the linguistic devices and context working together.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.